Multivariate Statistical and Multiproxy Constraints on Earthquake‐Triggered Sediment Remobilization Processes in the Central Japan Trench. (18th June 2020) - Schwestermann, T.; Huang, J.; Konzett, J.; Kioka, A.; Wefer, G.; Ikehara, K.; Moernaut, J.; Eglinton, T. I.; Strasser, M.
Abstract: Understanding the impact of earthquakes on subaqueous environments is key for submarine paleoseismological investigations seeking to provide long‐term records of past earthquakes. For this purpose, event deposits (e.g., turbidites) are, among others, identified and stratigraphically correlated over broad areas to test for synchronous occurrence of gravity flows. Hence, detailed spatiotemporal petrographic and geochemical fingerprints of such deposits are required to advance the knowledge about sediment source and the underlying remobilization processes induced by past earthquakes. In this study, we develop for the first time in paleoseismology a multivariate statistical approach using X‐ray fluorescence core scanning, magnetic susceptibility, and wet bulk density data that allow to test, confirm, and enhance the previous visual and lithostratigraphic correlation across two isolated basins in the central Japan Trench. The statistical correlation is further confirmed by petrographic heavy grain analysis of the turbidites and additionally combined with our novel erosion model based on previously reported bulk organic carbon 14 C dates. We find surficial sediment remobilization, a process whereby strong seismic shaking remobilizes the uppermost few centimeters of surficial slope sediment, to be a predominant remobilization process, which partly initiates deeper sediment remobilization downslope during strong earthquakes at the Japan Trench. These findings shed new light on source‐to‐sink transport processes in hadal trenches during earthquakes and help to assess the completeness of the turbidite paleoseismic record. Our results further suggest that shallow‐buried tephra on the slope might significantly influence sediment remobilization and the geochemical and petrographic fingerprints of the resulting event deposits. Plain Language Summary: Earthquakes can trigger widespread submarine sediment remobilization due to their strong ground shaking. The resulting deposits can be found over wide areas in subaqueous basin sequences, providing a clue to the recurrence pattern of major earthquakes. This is crucial information to assess seismic and tsunami hazards for civilization reliably. Our study uses, for the first time in submarine paleoseismology, a multivariate statistical approach based on geochemical and physical properties of sediments to improve event‐stratigraphic correlation in the central Japan Trench. We further confirm the statistical correlation by petrographic heavy grain analysis of sand bases within the event deposits. This data set is additionally combined with our novel erosion model based on age shifts between event deposits and background sediments of previously reported radiocarbon dates. Our results show that the major earthquakes mainly remobilize and move the upper few centimeters of surficial sediment from the slopes into the neighboring deeper basins. This finding holds the promise that sediment of the Japan Trench comprises a complete record of strong prehistoric earthquakes. We also find that tephra layers deposited on the slope before major earthquakes may significantly influence the sediment remobilization by earthquake shaking, as well as the resulting earthquake‐triggered deposits. Key Points: Multivariate statistics on XRF‐CS and MSCL data enhance the correlation of earthquake‐triggered event deposits in the Japan Trench Each event deposit reveals a characteristic geochemical, physical, and petrographic fingerprint Bulk organic carbon 14 C and the characteristic fingerprints of event deposits suggest predominantly surficial slope sediment remobilization